FIBER AND FAT INTAKE, SMOKING HABITS, BODY MASS INDEX AND CENTRAL OBESITY AND ITS ASSOCIATION WITH LIPID PROFILE OF MAN IN GATOT SUBROTO HOSPITAL HEART POLYCLINIC - Kevinti Febrina; Adhila Fayasari (Universitas Airlangga, 2020)
An increase in blood lipid profi le escalates risk of coronary heart disease (CHD). CHD is the leading cause of death in the world. This study was intended to analyze the relationship between fat intake, fi ber intake, smoking habits, Body Mass Index (BMI) and central obesity and lipid profi le among patients in cardiology clinic. This study used cross sectional design with 60 subjects aged >29 years who were outpatients in the Cardiaology Polyclinic at Gatot Soebroto Hospital. Central obesity was measured using metline by measurung waist circumference; BMI was converted from measurements of body weight and height; characteristics and smoking habits were taken using a questionnaire; and food intake was measured using Semi Quantitative FFQ. Lipid profi le data was collected through secondary data. Bivariate data analysis on categorical data used chi-square, Fisher-exact test or spearman ordinal correlation and stratifi cation analysis using ANOVA or kruskall-wallis. There were 78.3% subjects who had abnormal LDL, 76.7% had abnormal HDL, 80% had abnormal triglycerides and 78.3% had abnormal cholesterol. There were signifi ant relationship between fat intake, smoking habits, BMI and central obesity to the lipid profi le (LDL, HDL, triglycerides and cholesterol) (p <0.05). Fiber intake was not signifi cantly related to lipid profi le. However, based on stratifi cation analysis,the more fi ber intake the lower levels of LDL profi les, triglycerides and cholesterol, and the higher levels of HDL.